2020
DOI: 10.29303/jppipa.v6i1.340
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Dan Uji Daya Hambat Isolat Bakteri Endofit Bunga Tanaman Cengkeh (Syzygium aromaticum L.) Terhadap Bakteri Patogen

Abstract: This research was conducted to find out the capabilities of endophytic bacteria isolated from flowers of the clove plants in inhibiting the growth of bacteria Streptococcus mutans, Staphylococcus aureus, Klebsiella pneumoniae and Escherichia coli and to identify endophytic bacteria that potensial to produce an antibacterial. Stages of this research include the isolation of endophytic bacteria from flowers of the clove plants, antibacterial test, and molecular identification based on 16S rRNA. Isolates of endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
0
0
2
Order By: Relevance
“…These bacteria tend to be present as endophytes in the three pulp samples used, namely Aren, Coconut, and Sago, as normal flora. This study was in line with other studies, which found that one of the endophytic bacteria in rambutan fruit flesh was the genus that belongs to Staphylococcus [34].…”
Section: Figure 1 the Inhibitory Activity Of Isolate Endophytes Of E Coli Bacteriasupporting
confidence: 93%
“…These bacteria tend to be present as endophytes in the three pulp samples used, namely Aren, Coconut, and Sago, as normal flora. This study was in line with other studies, which found that one of the endophytic bacteria in rambutan fruit flesh was the genus that belongs to Staphylococcus [34].…”
Section: Figure 1 the Inhibitory Activity Of Isolate Endophytes Of E Coli Bacteriasupporting
confidence: 93%
“…Kondisi awal (pre) PCR diatur pada suhu 94°C selama 5 menit, kemudian diikuti dengan 35 siklus PCR yang terdiri dari denaturasi pada suhu 94°C selama 30 detik, annealing primer pada suhu 55°C selama 30 detik dan ekstensi pada suhu 72°C selama 45 detik. Setelah 35 siklus dilalui, selanjutnya dilakukan post PCR pada suhu 72°C selama 5 menit dan disimpan pada suhu 20°C (Sepriana et al, 2020)…”
Section: Identifikasi Molekuler Isolatunclassified
“…Kondisi awal (pre) PCR diatur pada suhu 94 o C selama 5 menit, selanjutnya diikuti dengan 35 siklus PCR yang terdiri dari denaturasi pada suhu 94 o C selama 30 detik, annealing primer pada suhu 55 o C selama 30 detik dan ekstensi pada suhu 72 o C selama 45 detik. Setelah 35 siklus terlampaui, dilakukan post PCR pada suhu 72 o C selama 5 menit dan disimpan pada suhu 20 o C (Sepriana et al, 2020…”
Section: Identifikasi Molekuler Isolat Bakteri Pelarut Fosfatunclassified